Generalized Chern–Pontryagin models - J. R. Nascimento; A. Yu. Petrov; P. J. Porfírio; Ramires N. da Silva (European Physical Journal C: Particles and Fields)
Abstract We formulate a new class of modified gravity models, that is, generalized four-dimensional Chern–Pontryagin models, whose action is characterized by an arbitrary function of the Ricci scalar R and the Chern–Pontryagin topological term $$ ^*RR$$ ∗ R R , i.e., $$f(R, ^*RR)$$ f ( R , ∗ R R ) . Within this framework, we derive the gravitational field equations and solve them for the particular models, $$f(R, ^*RR)=R+β ( ^*RR)^2$$ f ( R , ∗ R R ) = R + β ( ∗ R R ) 2 and $$f(R, ^*RR)=R+α R^2+β ( ^*RR)^2$$ f ( R , ∗ R R ) = R + α R 2 + β ( ∗ R R ) 2 , considering two ansatzes: the slowly rotating Schwarzschild metric and first-order perturbations of Gödel-type metrics. For the former, we find a first-order correction to the frame-dragging effect boosted by the parameter L, which characterizes the departures from general relativity results. For the latter, Gödel-type metrics hold unperturbed, for specific sort of perturbed metric functions. We conclude this paper by displaying that generalized four-dimensional Chern–Pontryagin models admit a scalar-tensor representation, whose explicit form presents two scalar fields: $$Φ $$ Φ , a dynamical degree of freedom, while the second, $$ϑ $$ ϑ , a non-dynamical degree of freedom. In particular, the scalar field $$ϑ $$ ϑ emerges coupled with the Chern–Pontryagin topological term $$ ^*RR$$ ∗ R R , i.e., $$ϑ ^*RR$$ ϑ ∗ R R , which is nothing more than Chern–Simons term.